CEMARAN PESTISIDA FOSFAT-ORGANIK DI AIR DANAU BUYAN BULELENG BALI - Putra Manuaba, I. B. (Jurnal Kimia (Journal of Chemistry); Vol. 2, No. 1 Januari 2008)
Pesticide is a chemical used to destroy or to control any pest that damages plant, animal, etc. Therefore, pesticide is very important for protecting plant, animal, and in controlling vector-borne diseases. The use of pesticide is therefore inevitable. A study to investigate the organophosphate pesticide residue in water of Lake Buyan was carried out. This is an expost facto study with Analytical Cross Sectional Study design. Sample preparation for this purposed was carried out following a standard method. Gas chromatography was employed in order to gain the organophosphate pesticide contaminant. Organophosphate pesticide contaminant, i.e. dimethoate, chlorphyrifos and prophenofos were observed on 55 water sampling point taken from 5 zone. The residual contaminant of dimethoate; chlorphyriphose; and prophenophose, were 9.3, 3.5, and 2.1 ppb respectively. Total residual contaminant was 14.9 ppb which was bellow threshold concentration of 100 ppb (SK Gubernur Bali No. 515 Tahun 2000).
Keywords: organophosphate pesticide, residual contaminant, expost facto